Citizenship education and human capabilities: lynchpin for sustainable learning environment and social justice - Tendayi Marovah (The Journal for Transdisciplinary Research in Southern Africa, 2013)
The paper builds on and contributes to literature in citizenship education studies in higher education. Many studies in this field have explored the history, development and implementation of various forms of citizenship formation as an advancement of social justice. However, little has been written on how the formation of critical democratic citizens 2 links with the notion of sustainable learning environments and how it relates to social justice. Studies by McKinney (2007); Waghid (2007; 2009), Lange (2012); and Leibowitz, Swartz, Bozalek, Carolissen, Nicholls &Rohleder(2012) are among those on citizen formation in the South African higher education context. Thisconceptual paper argues that the formation of critical democratic citizens through higher education relates not only to social justice, but also to the advancement of sustainable learning environments (SLEs) beyond physical spaces. The paper explores the normative value of a democratic education theory, Marion Young’s (1990) theory of justice and the politics of difference, and human development principles in advancing citizenship education. These foster both sustainable learning environments and social justice. A democratic education theory lays the foundation for an inclusive and deliberative form of education, while a theory of justice and politics of difference advances better justice and an environment that is non-oppressive. Human development principles set the tone for a sustainable human development, which becomes a framework through which asustainable learning environment is built in pursuit of social justice. Drawing on a Capabilities Approach framework and the philosophy of Ubuntu, with emphasis on substantive freedoms, opportunities, and the thriving of the common good, the paper illustrates how citizenship education advances a conception of sustainable learning environments and social justices not necessarily limited to physical spaces, distributive justice or economic motives, but inclusive of institutional arrangements, policy issues and relational justice.